Optimal monetary policy for a pessimistic central bank - Paolo Vitale (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2014)
We extend Svensson's (Svensson, 1997) model of optimal monetary policy to the case in which the monetary authorities are pessimistic. With respect to his formulation we show that: i) the inflation forecast is no longer an explicit intermediate target; ii) the monetary authorities move their instruments to hedge against the worst economic shocks, do not expect the inflation rate to mean revert to its first-best level and apply a more aggressive Taylor rule; and iii) the inflation rate is less volatile. Our conclusions also hold when the monetary authorities observe inflation and output gap with a time lag. Our analysis extends the analysis of van der Ploeg (van der Ploeg, 2009), as we allow for time-discounting of future social welfare losses due to deviations of output and inflation from first-best values.
Keywords: C61; E52; E58; 330; Monetary Policy; Pessimism; Discounted Linear Exponential Quadratic Gaussian